From the League of Nations to the UN: the history of the formation of universal international collective security organizations - Lisohorova, Kateryna; Svystun, Diana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
This work is devoted to the analysis of the history of the formation, achievements and failures of the League of Nations and the UN in the international arena. The factors that hindered or hinder the full realization of the potential of these global international collective security organizations were considered. And taking into account that the UN is the legal successor of the League of Nations on key foundations, principles, goals, and areas of activity, a historical parallel between them were drawn. As a result, the conclusions about similarities and differences in their structural, administrative, legal organization, and effectiveness were formulated. It was found that the first attempt to create a global organization aimed at the attainment of the international peace and collective security was unsuccessful as its founders had failed to form real levers of influence on the geopolitical situation in the world and to develop mechanisms for the prevention of armed conflicts. It was noted that subsequently, the desire of the international community to resolve disputes between countries by non-violent and diplomatic tools became a catalyst for the creation of an improved international organization aimed at consolidating the governments of countries around the world in the struggle for peace - the UN. It was shown the UN got some valuable lessons from the achievements and failures of its predecessor, but it still fails to ensure international peace and collective security fully. Indeed, the UN demonstrates the success rather in humanitarian activities than in political ones. It was emphasized that the issue of reforming the UN is being actively discussed in order to develop effective instruments of influence on the aggressor countries as the issues, related to the inviolability of borders, the preservation of the sovereignty of countries, and the achievement of collective security, are fundamental in the international arena.